Biosensors : new frontiers for the environmental analysis (2011)
ABSTRACT: Biosensors are very promising biotools useful for the fast, simple, cheap and reliable screening of many real samples. For their intrinsic features, these devices can find application in many different fields, but appear particularly useful for those requiring repeated analyses daily performed, such as biomedical, agricultural and environmental fields. This article reviews the biosensors which appeared useful for environmental analysis. In particular, the work focused on photosynthesis-based biosensors, i.e. biosensors whose biorecognition elements are represented by whole cells, or parts of cells, able to photosynthesize. An overview on this type of biosensors, included the methods to immobilize the biomediators and detect the pollutants, is given here along with the most recent examples of their application.